Is Code-Mixing Needed in English Teaching Process?: EFL Teacher's Experience - Dina Handrayani (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
This research investigates the EFL teacher's perspective of using code-mixing in EFL classes. The research design used narrative inquiry to uncover the story of the English teacher’s experience in using code-mixing, and a personal narrative was conducted by interview as the data. The results of the study indicate that: 1) the teacher's experience in teaching English which the teacher has many experiences in teaching at many different levels. 2) the teacher uses code-mixing because of the teaching method and the curriculum approach. The teacher needs code-mixing based on the student’s skills and the class circumstance.